2004 IEEE International Conference on Acoustics, Speech, and Signal Processing
DOI: 10.1109/icassp.2004.1325952
|View full text |Cite
|
Sign up to set email alerts
|

A locally weighted distance measure for example based speech recognition

Abstract: State-of-the-art speech recognition relies on a state-dependent distance measure. In HMM systems, the distance measure is trained into state-dependent covariance matrices using a maximum likelihood or discriminative criterion. This "automatic" adjustment of the distance measure is traditionally considered an inherent advantage of HMMs over DTW recognizers, as those typically rely on a uniform Euclidean distance. In this paper we show how to incorporate a non-uniform weighted distance measure into an examplebas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 6 publications
(6 reference statements)
0
23
0
Order By: Relevance
“…In [2] we showed that a class based weighted distance measure improves significantly over the more traditional Euclidean distance metric. In this paper we refine this approach with some ideas borrowed from the domain of non-parametric density estimation that explicitly compensate for the position of a reference vector in its class.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In [2] we showed that a class based weighted distance measure improves significantly over the more traditional Euclidean distance metric. In this paper we refine this approach with some ideas borrowed from the domain of non-parametric density estimation that explicitly compensate for the position of a reference vector in its class.…”
Section: Introductionmentioning
confidence: 98%
“…dynamic time warping (DTW), template based recognition or episodic modeling-as an alternative to HMMs [2,3,4,5]. Example based recognition offers a natural solution to some of the problems HMMs face, especially those related to long-term sequential modeling [5].…”
Section: Introductionmentioning
confidence: 99%
“…More attention to class-dependent distances is given in [10], where the goal is to learn weights for each feature/class combination, and to use these weights in a Mahalanobis-type metric. A similar approach is taken in [5] to improve performance in speech recognition. In [19], the authors propose learning different metrics for different classes and show that this improves classification results.…”
Section: Related Workmentioning
confidence: 99%
“…This may not be completely natural for a MIL problem, because we have some information about how positive bags are different from negative bags. In supervised learning problems where classes are expected to behave differently, class-dependent distances [10,5,19] or features [2,8] have been suggested. In this work we examine whether a similar approach might be reasonable for MIL problems.…”
Section: Introductionmentioning
confidence: 99%
“…In the TM-based approach, investigation has been recently carried out to estimate the parameters of the weighting matrix of the Mahalanobis distance to improve the performance. A maximum-likelihood estimation was described in [12] and a discriminative procedure was presented in [13]. However, these methods require a large amount of data to properly estimate the weights.…”
Section: Local Distancementioning
confidence: 99%